PELATIHAN GARAP IRINGAN DISANGGAR PEDALANGAN SERENGAN SURAKARTA - Sriyanto Sriyanto (Abdi Seni, 2016)
The learning condition of studio pedalangan Serengan which is not yet systematically arranged needs some improvements. therefore, it needs an activity of community service from academic staffs (lecturer 1 to increase the quality of puppetry learning especially the accompaniment treatment in order to make young generation more interested in it. The method used in the learning of pakeliran practice covers appreciation, giving speech, and demonstration. Based on the method, the activity had been held for 3 months. Two times a week, the trainer comes to build students for about three hours. The result is very interesting. The built students can master the materials given. The materials include the accompaniments of ada-ada greget saut nem, srepeg laras slendro pathet nem, ayak-ayakan laras slendro pathet nem, ayak-ayakan laras slendro pathet nem gong lima, lancaran manyar sewularas  slendro pathet manyura, ladrang sobrang laras slendro nem, ada-ada greget saut jugag, ayak-ayak tlutur laras slendro pathet nem Iringan pathet sanga wantahLadrang sri karongron laras slendro pathet sanga, srepeg laras slendro pathet sanga, ayak-ayakan laras slendro pathet sanga, sendhon tlutur, ada-ada greget saut sanga, sampak laras slendro pathet sanga, sampak laras slendro pathet manyura and ada-ada manyura Jugag.Key words: studio, puppetry, accompaniment